Isometric strength assessment in weightlifting - Varalda, C. (EWF Scientific Magazine, 2016)
When the decision was made to carry out the isometric deadlift test, some very important aspects were addressed in order to make the test effective as regards the analysis of the resulting numbers. Firstly, it was necessary to adapt the system to make the starting position as close as possible to that of the technical exercise. Then, it was necessary to define the type of grip required of the athlete, the "snatch" (a wider grip) or the "clean & jerk" (more narrow). Lastly, it was necessary to identify the precise moment in the exercise in which the barbell would be locked in order to measure the expressed force. The same iron platform used previously was adopted for the starting position; the only change made was a slight raise in the place where the feet are positioned so as to create a system that reduces the "run-up" to the bar. The "snatch" grip (wider one) was decided on, as it is considered less traumatic, and allows to anticipate the barbell lock.